DEALING WITH HETEROGENEOUS GROUPS: PROBLEMS AND SOLUTIONS - Sultonova Laylo Umidjon qizi (American Journals, 2023)
An analysis of the needs of representatives of heterogeneous groups of students is presented. Particular attention is paid to the needs of three categories of students – gifted, socially disadvantaged, and with disabilities. Recommendations are given for the development of vocational training and retraining programs.
Keywords: Gifted students, students with disabilities, growth needs, communication needs, subsistence needs, socially disadvantaged children.